PENENTUAN VEKTOR FILARIASIS DAN SPESIES MIKROFILARIA DI PUSKESMAS BATUMARTA VIII KABUPATEN OKU TIMUR TAHUN 2012 - Pahlepi, R. Irpan; Santoso, Santoso (Publikasi Penelitian Terapan dan Kebijakan, 2013)
Filariasis or elephantiasis is a disease caused by infection with the filarial worm which is transmitted by mosquitoes and can affect all groups regardless of age and gender. Batumarta VIII Health Center is one of the areas that are endemic filariasis in the district East OKU and Mf rate of 1.05%. This study aimed to confirm filariasis vector and species of microfilariae in the District of Batumarta VIII Health Center East OKU. The research was conducted during eight months (April- November 2012). Community with collection of blood finger were done at night to 502 people. Microfilaria positive were 4 people (Mf rate of 0.8%) with species Brugia malayi and the average density 200 / mL. Results 3 times catching mosquitoes 2792 which consists of 5 genera and 21species. The results of surgery for 34 mosquitoes did not reveal any L3 larvae within the mosquitoes. The suspect of filariasis vectors that found were Mansonia annulifera, Ma. Uniformis and Anopheles nigerrimus. Need for filariasis mass treatment activities since found a new case and have not done mass treatment in the study area.